Prevalence of amblyopia in congenital blepharoptosis: a systematic review and Meta-analysis - Jia-Ying Zhang; Xiao-Wei Zhu; Xia Ding; Ming Lin; Jin Li (International Journal of Ophthalmology, 2019)
AIM: To conduct a systematic review and Meta-analysis of the published literature to evaluate the pooled prevalence rate of amblyopia in patients with congenital ptosis. METHODS: We searched the PubMed, Embase, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Wanfang Data, and Chongqing VIP databases for studies reporting the prevalence of amblyopia in patients with congenital ptosis. The reference lists of relevant studies were scanned. Heterogeneity of effect sizes across studies was tested. We calculated prevalence ratios to compare prevalence estimates for different causes of amblyopia in patients with congenital ptosis, as well as for different geographical regions, year of publication and sample size in subgroup analyses. A systematic review and Meta-analysis were performed. RESULTS: We identified 29 eligible surveys with a total population of 2436. Prevalence rates of amblyopia ranged from 13.8% to 69%. We noted substantial heterogeneity in prevalence estimates for amblyopia in congenital ptosis (Cochran’s χ2 significant at P<0.0001; I2=90%). The pooled prevalence using random-effects models of 29 studies was 32.8% (95%CI: 27.3%-38.4%) in the overall population. Compared to the overall pooled prevalence, amblyopia prevalence was higher in studies in which only subjects with blepharophimosis syndrome were included. CONCLUSION: We confirm that nearly one-third of congenital ptosis patients are suffering from or at risk for amblyopia. Patients with blepharophimosis syndrome are more likely to develop amblyopia. The identification and management of amblyopia should be integral to the treatment of congenital ptosis.